Green concrete made from biomass waste and glass waste (2022)
The improvement in the physical characteristics of green concrete, as well as the environmental benefits of the innovative use of RHA (rice husk ash) as a cement replacement motivate further study in concrete manufacturing. The fresh and hardened properties of traditional concrete show significant improvement with the inclusion of WG glass residues. In this work, cylindrical specimens with dimensions of 0.1 m in diameter and 0.2 m in height were prepared. The fresh (depression) and hardened (density and compressive strength) properties were studied. Modified concretes were prepared with replacements of 5% of calcined rice husk and with the incorporation of glass residues replacing the cement. Different rice ashes were prepared: residual glass mass ratio 1: 0, 1: 1, 1: 2 and 1: 3. According to the experimental results, the fall of the concrete mixture increased with an increase in glass waste, in fact, glass waste has a lower water absorption, this may be the reason for better workability results. Additionally, the experimental results showed that the incorporation of glass residues in concrete prepared with rice ash is not related to the final density of concrete specimens due to the similar density between cementitious materials. The compressive strength of concrete shows a significant difference with the inclusion of waste glass. The 1:3 sample was the optimal concrete mixture. This compressive strength was observed up to 15%. The experimental results show that the addition of waste glass to the concrete mixture prepared with rice ash improves mechanical properties and may be a potential option to mitigate the impact of municipal biomass waste.